The Best American Newspaper Narratives of 2012 - Saslow, Eli; Getschow, George, 1950- (Book collections on Project MUSE., 2014)
"This anthology collects the ten winners of the 2012 Best American Newspaper Narrative Writing Contest at the Mayborn Literary Nonfiction Conference, which is hosted by the Frank W. Mayborn Graduate Institute of Journalism at the University of North Texas. The contest honors exemplary narrative work and encourages narrative nonfiction storytelling at newspapers across the United States. First place winner: Eli Saslow, "Life of a Salesman," published by the Washington Post, is about a swimming pool salesman experiencing the unraveling of his decades-long success story"--Publisher's annotation.